Efficacy and Safety of Standard‐Dose Versus Half‐Dose Tirofiban in Patients with Non‐ST Elevation Acute Coronary Syndromes Undergoing Early Percutaneous Coronary Intervention. Issue 4 (18th July 2013) - Li, Wei; Fu, Xianghua; Xue, Haiwei; Wang, Yanbo; Wang, Xuechao; Zhao, Yujun; Geng, Wei; Yang, Zengxin; Gu, Xinshun; Hao, Guozhen; Jiang, Yunfa; Fan, Weize; et al.
Summary Introduction To explore the optimal dosage of tirofiban associated with double benefits of efficacy and safety in patients with non‐ST elevation acute coronary syndromes (NSTE‐ACS) undergoing early percutaneous coronary intervention (PCI). Aims A total of 163 patients were included in this study (78 in SD group versus 85 in HD group). In SD (HD) group, tirofiban was administered intravenously with a bolus dose of 10 (5) μg/kg within 3 min and followed by continuous intravenous infusion of 0.15 (0.075) μg/kg/min for 48 h. Within 24 h on admission, patients underwent CAG or CAG+PCI. The angiographic results (initial TIMI, final TIMI/CTFC/TMPG) were evaluated. Platelet aggregation rate (PAR) was measured before and 2, 24, 48 h after bolus tirofiban. MACEs were evaluated at 7‐day, 30‐day, and 6‐month follow‐up. Bleeding was observed at 7 days. Results The proportions of TIMI grade 3 seemed higher in SD group before and after PCI followed by a better myocardial perfusion, but not statistically different (P = 0.26/0.08). PAR was lower in SD group than that in HD group at 2 h after bolus tirofiban (P = 0.03). MACEs were not statistically different at 7, 30 day, and 6 month in two groups. The incidence of minor bleeding was significantly lower in HD group than that in SD group (8.2% vs. 20.5%, P = 0.04). The risk of bleeding would increase under the conditions of decreased PAR, increased dose of tirofiban and decreased CCr. Conclusion Half‐dose tirofiban was not inferior to standard‐dose in efficacy, what is more, half‐dose tirofiban showed a better safety characteristic of lower bleeding risk. Therefore, half‐dose tirofiban is recommended to patients with NSTE‐ACS undergoing early PCI.